Rubber Strap Quality Improvement by Optimization of Tensile Strength and Time Curing Using Response Surface Methodology - Erwanto, Jefri; Su’ef, Mok. (Institut Teknologi Sepuluh Nopember, 2019)
This paper will demonstrate combination of optimum response for Tensile strength and Time curing which are obtained by combining elastomer, filler and co-accelerator at optimum level factors is the best way to overcome defect products. Data from this study will be obtained from 15 direct experiments based on RSM by using box-behnken design-Minitab 18 and response optimization was performed to get optimal response value combination from the expected target response. The analysis shows that all factors including elastomer, filler and co-accelerator have significant effect on tensile strength and time curing responses. The best composition to get the optimal combination of responses from certain response limits is elastomer = 70PHR, filler = 30PHR, and co-accelerator = 1.47PHR. The optimum value for tensile strength response is 15 kg/cm2 and time curing is 3.5 minutes. Beside as a solution for this problem, this optimization will increase production capacity of rubber strap 12.5% more that the factory decide to decrease production line and choose market development strategy to overcome access production and labor to new product base on polyurethane